(untitled) (El Taco en la Brea, 2023)
Based on the analysis about the confidence in the revolutionary utopia that the communist poetics of the 20th century reflect and its contrast with a dystopian present in which has dissipated that future horizon announced by these poetics, this paper proposes a critical reflection on the current research work as a «melancholic exercise». It takes as a trigger a Robert Desnos poem dedicated to Raúl González Tuñón in 1937, during the Second Congress of Intellectuals for the Defense of Culture, to investigate some specific artistic, political and theoretical moments of a barely outlined history of successive beginnings and endings of the utopian future.